Psychosocial Predictors of Sexual Abstinence among Senior Secondary School Students in an Urban Setting in the Southwest Region of Cameroon - EE, Tarkang; MM, Nzegge; E, Dadah; EH, Ngondihiack; SM, Dzah; F, Adu-Poku; SY, Ahiabor; LB, Pencille (Journal of Clinical Research In HIV AIDS And Prevention, 2017)
Background: In the absence of a cure for HIV and AIDS, prevention remains the most effective strategy to eliminate the pandemic. Abstinence from sexual intercourse is, therefore, the primary prevention weapon among unmarried adolescents and young adults, especially the school-going ones. This study uses the main constructs of the Health Belief Model (HBM), as the theoretical framework to investigate the psychosocial predictors of sexual abstinence among senior secondary school students in an urban setting in the Southwest region of Cameroon Methods: This study adopted a cross-sectional design, collecting data from a stratified random sample of 420 students in November 2016, using a pretested structured questionnaire, and analyzing them using SPSS version 20 software programme, using binomial logistic regressions at the level 0.05. Results: Only 194 (46.2%) were abstaining from sex. Perceived susceptibility to HIV, perceived severity of HIV/AIDS, perceived benefits of sexual abstinence and perceived self-efficacy for sexual abstinence were not that high, 79.8%, 71.0%, 86.4% and 68.3% respectively. None of the above constructs of the HBM was a significant predictor of sexual abstinence. However, increasing age was significantly associated with an increased likelihood of sexual abstinence, OR=1.6 (95% CI 1.20-2.24, p=0.002). Conclusions: Senior secondary school students in urban Cameroon were not practicing sexual abstinence. Interventions and strategies to increase sexual abstinence are highly recommended and should focus on increasing the perception of risk of contracting HIV, which is assumed to be the immediate antecedent of sexual abstinence, on overcoming barriers to sexual abstinence and on sexual abstinence negotiating skills, and should target adolescent students (10-19 years old).
Keywords: Health Belief Model (HBM); HIV/AIDS; Senior secondary school students; Sexual abstinence; Southwest region; Urban Cameroon.